The Wampanoag - Cunningham, Kevin, 1966-; Benoit, Peter 1955- (New York : Children's Press, 2011)
An exploration of the Wampanoag Indians, discussing the nation's relationship with settlers, culture, women, housing, and more.
W
900
W
Keywords: Wampanoag Indians -- Juvenile literature